Less is more revisited: association with global multiparty session types - Yoshida, N; Hou, P (Springer, 2024)
Multiparty session types (MPST) [12] provide a type discipline where a programmer or architect specifies a whole view of communications as a global protocol, and each distributed program is locally type-checked against its end-point projection. After 10 years from the birth of MPST, Scalas and Yoshida [18] discovered that the proofs of type safety in the literature which use the end-point projection with mergeability are flawed. After this paper, researchers wrongly believed that the end-point projection (with mergeability) was unsound. We correct this misunderstanding, proposing a new general proof technique for type soundness of multiparty session π-calculus, which uses an association relation between a global type and its end-point projection.